Lineamientos para una evaluación de docentes - Coloma Manrique, Carmen Rosa (2013)
This document aims to be a reflection on the evaluation of teachers which expects to throw light on aspects related to the conception of this kind of evaluation, its link to the educational institution, and the improvement of quality. This article also tries to clarify the purposes of evaluating teachers, as well as to set up some general guidelines to be considered.